Analysis of caesarean sections according to modified Robson’s ten group classification system at a tertiary care centre in Western India - Jogia, Priyanka D.; Lodhiya, Kaushik K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The increasing trends for Caesarean section (CS) in India and worldwide have been a cause of concern. The aim is to compare and analyse CS rates across the globe, WHO recommends the Robson’s ten group classification system (TGCS). This will help to target appropriate group of women for reduction of overall CS rates. Methods: This was a retrospective study design using hospital records for women delivered in December 2017. Data was entered and analysed using excel 2007 and presented using modified Robson’s ten group classification system. Results: Out of total 650 women delivered during the study period, 184 (28.3%) delivered by CS. Group 1 and group 2 included a total of 49.53% women in the present study. The CS rates varied from 100% in group 5 (previous CS), group 7 (breech, multiparous) and group 9 (abnormal lie) to as low as 0.9% in group 3. The present study highlights that group 5 i.e. women with previous CS, contributed maximum (37%) to the overall surgical deliveries with group 2 being the second largest contributor (21%). Conclusions: The findings of the study indicate that group 5-women with prior CS and group 2-women with induced labour contributed maximum to overall CS rates. TOLAC should be a routine and not optional. Simultaneously Judicious selection of women for induction, strict implementation of induction protocols to decrease the cases of failed inductions will also reduce primary CS. To monitor the CS rates and take appropriate actions it is recommended that Robson’s TGCS be used continuously in all health institutions.